Binding and Selectivity of Halides with Macrocyclic polyamines - Hossain, Md. Alamgir (2009)
This review covers the binding and selectivity aspects of halide anions in positively charged polyammonium hosts including monocyclic, bicyclic and tricyclic systems. The binding affinity and selectivity of host molecules for halides are largely depended on the shape, charges, and ring size of the host molecules. In general, a monocycle that has a flexible cavity binds an anion from both side, however a bicyclic or tricyclic molecule tends to bind a single anion in its cavity.